2022
DOI: 10.1111/vco.12803
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography of lymph nodes in dogs with head and neck cancer: A pilot study

Abstract: Shear wave elastography (SWE) is a novel ultrasound imaging technique, used in human medicine to differentiate metastatic from non‐metastatic lymph nodes (LNs) based on higher tissue stiffness. The objective of this pilot study was to evaluate whether canine metastatic LNs were stiffer compared to non‐metastatic LNs. SWE of sentinel or regional LNs in dogs with head and neck cancer was performed. Ten elastograms of each LN were acquired. In each elastogram, mean, median, and maximum shear wave velocities (SWVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Our findings suggested that the values of E-max, E-mean, and E-min in the adenoma group were significantly higher than those in the hyperplasia group, indicating that the hardness of parathyroid adenoma was greater than that of parathyroid hyperplasia, which is consistent with the pathological changes. [14,15] The results indicated that the volume, blood flow, PTH concentration, and elastic modulus of the joint focus were of high value in diagnosing parathyroid adenoma. The AUC was 0.892 (P < .001), sensitivity was 78.9%, specificity was 97.4%, and ultrasonic elastic imaging was a simple, operator-independent, repeatable method.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings suggested that the values of E-max, E-mean, and E-min in the adenoma group were significantly higher than those in the hyperplasia group, indicating that the hardness of parathyroid adenoma was greater than that of parathyroid hyperplasia, which is consistent with the pathological changes. [14,15] The results indicated that the volume, blood flow, PTH concentration, and elastic modulus of the joint focus were of high value in diagnosing parathyroid adenoma. The AUC was 0.892 (P < .001), sensitivity was 78.9%, specificity was 97.4%, and ultrasonic elastic imaging was a simple, operator-independent, repeatable method.…”
Section: Discussionmentioning
confidence: 98%
“… 7 , 8 SWV is reported in meters per second, and its elevation shows a higher elastic modulus in the organ. In veterinary medicine, these investigations were used in previous studies to predict hepatic fibrosis, 9 discriminate metastatic and nonmetastatic lymph nodes, 10 evaluate renal tissue stiffness, 11 distinguish benign and malignant mammary gland neoplasms, 12 and in dogs with extrahepatic biliary obstruction. 13 In addition, a recent veterinary research evaluated the influence of anesthesia to a hepatic elastic modulus measured by 2D‐SWE; however, the results have been inconsistent, with a study reporting a higher elastic modulus in anesthetized than in awake dogs, 14 and another showing the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…14 There are multiple recent studies evaluating the role of shear wave elastography in veterinary medicine, including the liver in healthy dogs 15 and cats 16 as well as hepatic fibrosis in dogs. 17 Shear wave elastography has also been used to evaluate sentinel lymph nodes 18 in dogs.…”
Section: Introductionmentioning
confidence: 99%